Zu kreativen Ausdrucksformen im deutschsprachigen öffentlichen Raum - Anna Dargiewicz (Colloquia Germanica Stetinensia)
“Linguistic landscape research is a relatively young sociolinguistic subdiscipline”, stated Peter Backhaus in 2007. The research field of Linguistic Landscape, also referred to as LL, deals with the language visible in public space. The aim of the article is to prove this on the basis of the collected corpus that the city is not only a place of oral communication, but also a space where people communicate by means of the written word. Moreover, the texts present in public space are a confirmation of the creativity of the users of the German language, which is illustrated by the corpus obtained with the help of the Linguistic Landscape research. This creativity is reflected in the formation of linguistic forms, which are formed using the familiar rules of German word formation. These word formations are striking, surprising or thought-provoking due to their peculiarity, thus arousing the interest of the readers/viewers. They are linguistic neologisms and at the same time they prove that there is a need in society for increasingly striking communication patterns, whereby words/word-forming morphemes are combined in unusual, hitherto unexplored ways. As a result, the information communicated undoubtedly attracts more attention from the recipients.